2021
DOI: 10.3390/vaccines9121428
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of COVID-19 Vaccine Acceptance and Hesitancy among Healthcare Workers in Southern California: Not Just “Anti” vs. “Pro” Vaccine

Abstract: In this study, we evaluated the status of and attitudes toward COVID-19 vaccination of healthcare workers in two major hospital systems (academic and private) in Southern California. Responses were collected via an anonymous and voluntary survey from a total of 2491 participants, including nurses, physicians, other allied health professionals, and administrators. Among the 2491 participants that had been offered the vaccine at the time of the study, 2103 (84%) were vaccinated. The bulk of the participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 44 publications
3
35
0
12
Order By: Relevance
“…This likely occurs to some degree for most individuals, as people tend to interact with those who share similar values and ideas; however, behavioral studies have shown that suspicion and fear decrease, and a more meaningful exchange of ideas between opposing sides can be facilitated by ex-tended contact. Family or household size was also related to vaccine hesitancy, with larger households being associated with higher rates of hesitancy [110]. Interestingly, HCWs with children were more likely to vaccinate themselves [124,125].…”
Section: Demographics Of Vaccine Hesitant Hcwsmentioning
confidence: 99%
See 3 more Smart Citations
“…This likely occurs to some degree for most individuals, as people tend to interact with those who share similar values and ideas; however, behavioral studies have shown that suspicion and fear decrease, and a more meaningful exchange of ideas between opposing sides can be facilitated by ex-tended contact. Family or household size was also related to vaccine hesitancy, with larger households being associated with higher rates of hesitancy [110]. Interestingly, HCWs with children were more likely to vaccinate themselves [124,125].…”
Section: Demographics Of Vaccine Hesitant Hcwsmentioning
confidence: 99%
“…Hesitancy has also been noted among HCWs in the military [108] and at rural hospitals [109]. One study found that the only hospital department or setting associated with higher rates of vaccination worked in the intensive care unit (ICU) [110]. Thus, direct exposure to the severe COVID-19 illness, such as in the ICU, may be a stronger motivator for vaccination.…”
Section: Demographics Of Vaccine Hesitant Hcwsmentioning
confidence: 99%
See 2 more Smart Citations
“…We designed the survey to achieve two distinct goals: 1) analyze HCW attitudes toward COVID-19 vaccination to identify clusters or groupings predisposed to vaccine hesitancy, which in turn might aid in tailoring vaccine education programs (reported in another manuscript); [40] and 2) assess the practical work-related impacts of vaccine-associated side effects, which might assist health employers in planning future vaccination booster schedules (the focus of the present report). A working group developed the measures, and the survey was based on previous questionnaires conducted amongst the 2009 H1N1 flu pandemic.…”
Section: Methodsmentioning
confidence: 99%